Anatomical, histochemical, and developmental approaches reveal the long-term functioning of the floral nectary in Tocoyena formosa (Rubiaceae) - Izquierdo, Juliana V. [UNESP]; Canaveze, Yve; Machado, Silvia Rodrigues [UNESP]; Amorim, Felipe W. [UNESP] (Springer Nature, 2024)
Tocoyena formosa has a persistent floral nectary that continues producing nectar throughout flower and fruit development. This plant also presents an intriguing non-anthetic nectary derived from early-developing floral buds with premature abscised corolla. In this study, we characterize the structure, morphological changes, and functioning of T. formosa floral nectary at different developmental stages. We subdivided the nectary into four categories based on the floral and fruit development stage at which nectar production started: (i) non-anthetic nectary; (ii) anthetic nectary, which follows the regular floral development; (iii) pericarpial nectary, derived from pollinated flowers following fruit development; and (iv) post-anthetic nectary that results from non-pollinated flowers after anthesis. The nectary has a uniseriate epidermis with stomata, nectariferous parenchyma, and vascular bundles, with a predominating phloem at the periphery. The non-anthetic nectary presents immature tissues that release the exudate. The nectary progressively becomes more rigid as the flower and fruit develop. The main nectary changes during flower and fruit development comprised the thickening of the cuticle and epidermal cell walls, formation of cuticular epithelium, and an increase in the abundance of calcium oxalate crystals and phenolic cells near the vascular bundles. Projections of the outer periclinal walls toward the cuticle in the post-anthetic nectary suggest nectar reabsorption. The anatomical changes of the nectary allow it to function for an extended period throughout floral and fruit development. Hence, T. formosa nectary is a bivalent secretory structure that plays a crucial role in the reproductive and defensive interactions of this plant species.
Keywords: Nectar; Nectary lifespan; Non-anthetic nectary; Ontogeny; Post-floral secretion; Structure